The effect of entrepreneurial orientation on innovation performance in the airport industry through learning orientation and strategic alignment - Samer Ali Al-Shami; Ali Khalifa Mohamed Salim Alsuwaidi; Suriati Akmal (Cogent Business & Management, 2022)
In a highly competitive market and global economy, innovation is often recognised as the pinnacle of success and one of the most critical components. Entrepreneurial orientation has been recognised as an effective development strategy to advance innovation performance. Nevertheless, innovation research in the airport industry through entrepreneurial orientation has not received adequate attention. In addition, the development of innovation requires a dynamic change in strategic alignment and learning capacity. Nonetheless, the literature still lacks studies explaining how entrepreneurial orientation influences innovation performance through strategic alignment and learning orientation in the airport industry. Therefore, the present study aimed to examine the relationship between entrepreneurial orientation and innovation performance through the mediating effect of strategic alignment and learning orientation in the Dubai airport. A questionnaire was distributed to 413 employees from three main departments. The research findings revealed a significant positive relationship between entrepreneurial orientation and innovation performance. The findings also exposed that strategic alignment and learning orientation mediate the above relationship. Theoretically, this study extends the dynamic capabilities theory by providing an empirical model explaining how to dynamically improve innovation performance in the airport through the entrepreneurial orientation mediated by strategic alignment and learning orientation. Practically, this study also introduces a model that assists the managers in developing employees' entrepreneurial capabilities and airport information technology (IT) alignment and learning that are important to improve airport innovation performance.
Keywords: 650; performance; innovation; alignment; Entrepreneurial; learning; orientation